Concomitant Chemotherapy and Radiotherapy in the Adjuvant Treatment of Breast Cancer - Faria, Sergio L. (2001)
Introduction: The conventional treatment of localized breast cancer involves the use of both systemic therapy and loco-regional radiation after surgery. The ideal sequence of these two treatments is still undefined. This paper focus on our experience of concomitant chemotherapy (CT) and radiotherapy (RT), and discusses information from the literature about this issue. Material and Methods: Between Jan,1989 and Jan, 1999 a retrospective analysis of 103 patients with ductal carcinoma of the breast who received concomitant CT with cyclophosphamide, methotrexate and 5 fluouracil (CMF) and RT was made. Radiation did not included mammary chain or axilla and total dose was of 50Gy. End points were tolerance and toxicity leading changes to doses. Results: Mean age was 44y; median follow up time of 33 mo; 62 patients had breast conserving surgery and 41 had mastectomy. All patients received both treatments without a break or dose modification. There was no change or interruption of RT. Ten out of 103 patients had the prescribed dose of CT decreased of 10%-20%. There was no evident changes in cosmetic results. Discussion: Most of the knowledge regarding the delay of CT or RT comes from retrospective studies, and results are conflicting. It is well accepted that high risk patients need both CT and RT. However, there are data suggesting that giving RT first and CT after may increase the rate of distant metastases. There are also studies showing worse impact in the local control with the delay of radiotherapy. The use of concomitant chemotherapy and radiotherapy has apparent advantages, but no randomized trial has addressed this issue yet. Our experience has shown that is possible to give concomitant CT with CMF and RT without irradiation of IMC and axilla without major changes in scheduling or dose of both therapies.